The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/ac049434t
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization of Surface-Bound Peptides for Mass Spectrometric Detection via Threshold Single Photon Ionization

Abstract: Chemical derivatization of peptides allows efficient F2 laser single photon ionization (SPI) of Fmoc-derivatized peptides covalently bound to surfaces. Laser desorption photoionization mass spectrometry using 337-nm pulses for desorption and 157.6-nm pulses for threshold SPI forms large ions identified as common peptide fragments bound to either Fmoc or the surface linker. Electronic structure calculations indicate the Fmoc label is behaving as an ionization tag for the entire peptide, lowering the ionization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…More recently, it has been suggested that the tagging of large biomolecules with light chromophores can facilitate their detection [25]. This idea has also been corroborated in our own studies on the photo-detection of large neutral amino acid and nucleotide clusters [26].…”
Section: Introductionsupporting
confidence: 62%
“…More recently, it has been suggested that the tagging of large biomolecules with light chromophores can facilitate their detection [25]. This idea has also been corroborated in our own studies on the photo-detection of large neutral amino acid and nucleotide clusters [26].…”
Section: Introductionsupporting
confidence: 62%
“…Even better, the use of 7.87-eV LDPI-MS with a low-IE tag (dimethyl amino benzene) coupled to the bisphenol A derivative led to strong signal enhancement (43). Tagging a covalently bound surface analyte with a low-IE species also permitted detection of small peptides covalently bound to an oxide via a siloxane linker (32). …”
Section: Spi For Surface Analysismentioning
confidence: 99%
“…A home built laser desorption vacuum ultraviolet (VUV, 118 nm) postionization linear time‐of‐flight mass spectrometer (LDPI MS) is used for surface analysis of the model system. The advantage of VUV postionization in LDPI MS is that it enhances ionization yields with a minimum of fragmentation 14–16. LDPI MS is used to verify the preparation steps of the model dental composite by chemical analysis of the methacryloyl overlayer, Bis‐GMA‐methacryloyl overlayer, and several control surfaces.…”
Section: Introductionmentioning
confidence: 99%